TM/Landsat-5 bands in the discrimination of wheat and bean crops - Epiphanio, José Carlos Neves; Formaggio, Antônio Roberto; França, Geraldo Victorino de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to assess the potentia of the six reflective TM/Landsat-5 bands for discriminating between wheat (Triticum aestivum L.) and bean (Phaseolus vulgaris L.) fields. Fifteen fields of both crops wheat and bean were selected in São Paulo State - Brazil region, for which three multidate cloud free TM sets were acquired during the winter growing season of 1986. Digital numbers were sampled for the 30 fields and corrected for additive effects before being transformed into reflectance values. These values were used for calculating the EAC index which expresses the potential of each TM band for spectral discrimination between wheat and bean fields. The TM7 was the best band; TM2, TM3 and TM5 were intermediarty; and TM1 and TM4 were in the last position. The vegetative phase was more appropriate than the reproductive phase of biologic cycle as far as wheat and bean discrimination is concerned. The comparison between simulated reflectance data from a canopy reflectance model and real satellite reflectance data agreed very well except for TM7 band. A need for more detailed investigation about the reflective properties and the discrimination potencial of the TM7 spectral band was aroused.